La sostenibilidad del cultivo de espárragos verde en centro poblado Macabí Alto, Razuri - La Libertad 2015 - 2016, a través del desarrollo de ventajas competitivas - Pérez Vargas, Ana Claudia (2017)
The main objective of this research is to analyze the essential factors for the achievement of the sustainability of green asparagus cultivation in the Macabí Alto town center through the use of comparative advantages and the development of competitive advantages through the implementation of the Irrigation Technified system and Direct Marketing system. This allowed us to contrast economic theory with reality, as well as develop mechanisms to achieve the competitiveness of one of the main agro-export products, creating a sustainable position of the crop over time and improving the quality of life of farmers. The analysis was carried out using the main econometric and economic indicators. The methodology that was used both to obtain information and to analyze the data obtained, involved collecting data through a survey applied to the 38 hectares of asparagus cultivation under study as a survey to the owners of these. It also uses the econometric package EViews to measure how much the use of each input influences production. The results show that for the achievement of sustainability it is necessary to develop competitive advantages such as the implementation of technological and commercial improvements, however it is not enough, it requires a joint action between the local government, community, non-governmental organizations and exporting companies.